The Sucrose Contents of Four Honey Types from Apis mellifera Beekeepers in Java - Adalina, Yelin; Kuntadi, Kuntadi (El-Hayah : Jurnal Biologi, 2019)
Honey is a sweet thick liquid made by honeybees as their main products. Due to the increasing demand for honey, the risk of counterfeiting is on the rise, mainly when the production is limited. In term of quality standards, the sucrose content is one of the benchmarks in determining the authenticity of honey. This study aims at determining the sucrose contents of the honey from six regencies in Java. Ten honey samples that consisted of two samples of kapok honey, three samples of mango honey, three samples of rubber honey, and two samples of coffee honey were obtained fromÂ Apis melliferaÂ beekeepers. The results showed that the averages of sucrose contents in mango honey, rubber honey, coffee honey, and kapok honey were respectively 4.94%, 3.47%, 10.49%, and 1.02%. The sucrose contents of the ten honey samples averagely met the benchmark. Still, two honey samples exceeded the criterion outlined in SNI-2013 (maximum of 5%), i.e., mango honey from Sragen Regency and coffee honey from the Pasuruan Regency. The high sucrose content of coffee honey was allegedly induced by honey counterfeiting through the addition of sugar solutions.